Quantitative binomial distribution analyses of nanoscale like-solute atom clustering and segregation in atom probe tomography data - Moody, Michael P.; Stephenson, Leigh T.; Ceguerra, Anna V.; Ringer, Simon P. (Microscopy research and technique, 2008)
The applicability of the binomial frequency distribution is outlined for the analysis of the evolution nanoscale atomic clustering of dilute solute in an alloy subject to thermal ageing in 3D atom probe data. The conventional χ2 statistics and significance testing are demonstrated to be inappropriate for comparison of quantity of solute segregation present in two or more different sized system. Pearson coefficient, μ, is shown to normalize χ2 with respect to sample size over an order of magnitude. A simple computer simulation is implemented to investigate the binomial analysis and infer meaning in the measured value of μ over a series of systems at different solute concentrations and degree of clustering. The simulations replicate the form of experimental data and demonstrate the effect of detector efficiency to significantly underestimate the measured segregation. The binomial analysis is applied to experimental atom probe data sets and complementary simulations are used to interpret the results. Microsc. Res. Tech., 2008. © 2008 Wiley‐Liss, Inc.